Processing plants damage mechanisms and on-stream inspection using phased array corrosion mapping—a systematic review - Tai, Jan Lean; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani (Universiti Putra Malaysia Press, 2024)
This review aims to study the process plant damage mechanisms published by previous research, such as general corrosion, localised corrosion, and stress corrosion cracking. This review was conducted by analysing the current application of the common inspection method and technique and focusing on the phased array ultrasonic testing application. In order to further the current study, the review seeks direction on evaluating phased array corrosion mapping techniques to detect corrosion and metal loss during plant operation and minimise the plant’s need for maintenance. This systematic literature review provides a better understanding of the current damage mechanisms and shows the possibility of an extended future study.